Suicide trends during COVID-19 pandemic in Gunungkidul, Indonesia - F A Nurdiyanto; Valendra Granitha Shandika Puri; Lisa Sunaryo Putri (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
The COVID-19 pandemic had a tremendous impact on psychological burdens and may lead to suicide acts. Suicide is a global mental health problem that happens all over the world. This study was conducted to evaluate the effect of the COVID-19 pandemic on the suicide rates and estimate the category of male-female suicides. This study analyzed suicide data from the Gunungkidul Resort Police from April 2018 to April 2021. Gunungkidul Regency is one area in Indonesia with a high suicide rate. From that time of period, there were about 97 suicide cases as the sample of this study. This article estimated the suicide trend using time series forecasting and Chi-square tests to find potential differences before and after the outbreak. Chi-square analysis showed that there was no difference in the pattern of suicide before and since the COVID-19 pandemic (????2 = 12.05; p > 0.05), as well as the male rates (????2 = 20.17; p > 0.05). However, suicide among females has increased since the outbreak (????2 = 23.43; p < 0.05), especially among the elderly. This article recommended providing a support system, strengthening social networks, and widening the access of women and the elderly to health and psychological services during the pandemic.